Effects of Four Yeasts on the Quality of Kiwifruit Wine Made Using Different Cultivars - Shuo ZENG; Xinyu GUO; Dongsheng NIU; Feng LI (Shipin gongye ke-ji)
In this study, the fermentation of kiwifruit wine (prepared using five kiwifruit cultivars, Xuxiang, Hayward, Huayou, Jinyan, and Hongyang) with four Angel yeast strains (ADT, CECA, VIC, and BV818) was investigated. The impact of yeast on the quality of different kiwifruit wines was compared by measuring parameters such as total sugar, alcohol content, total flavonoid, and total phenolic contents. The results showed that alcohol content of all the kiwifruit wines after fermentation ranged from 7.30% to 9.20% v/v, classifying them as low-alcohol wines. The Huayou kiwifruit wines fermented with yeast strains VIC and BV818 showed better color characteristics. The wine fermented with VIC yeast from Huayou kiwifruit had the highest total phenolic content (1140.11 mg GAE/L) and exhibited strong DPPH radical scavenging activity (96.46%). The wine fermented with BV818 yeast from Huayou kiwifruit had the highest total flavonoid content (1186.80 mg RE/L) and demonstrated a strong ferric ion reducing power (10.34 mmol Trolox/L), while the BV818-fermented wines also showed a strong ability to scavenge the ABTS+ radical. Additionally, the wine fermented with ADT yeast from Huayou kiwifruit exhibited the highest ferric ion reducing power (12.83 mmol Trolox/L). After fermentation, ellagic acid was the dominant monomeric phenol in all kiwifruit wines, and all wines demonstrated strong in vitro antioxidant activities. In sensory evaluations, the Huayou kiwifruit wine fermented with VIC yeast received higher scores for aroma, flavor, and typicality. This study provides a theoretical basis for selecting optimal yeast strains and cultivars for kiwifruit wine production.